ACCOUNTABILITY TRAINING AND ASSISTANCE BASED ON DIGITAL ACCOUNTING INFORMATION SYSTEMS IN CUPAK VILLAGE, JOMBANG REGENCY - Cholis Hidayati; Ardhi Islamudin (DIA: Jurnal Administrasi Publik, 2023)
Micro, small and medium enterprises (MSMEs) do not understand the importance of accountability, they have not been able to compile financial reports based on financial accounting standards for micro, small and medium entities (SAK EMKM), and the use of digital technology in compiling financial reports has not been utilized properly by MSME actors. This community service activity aims to increase the perception of MSME actors in Cupak Village, Ngusikan District, Jombang Regency, East Java Province on the urgency of financial accountability for the business they run along with literacy in the application of SAK EMKM using user-friendly digital accounting media. The method uses lectures, training and mentoring, the object of community service activities is MSME actors in Cupak Village, Ngusikan District, Jombang Regency, East Java Province. The results achieved from this activity are an increased understanding of the importance of business accountability and the implementation of financial records in accordance with SAK EMKM with user-friendly digital accounting media. Matching fund program training made MSME actors in Cupak Jombang understand the importance of accountability, this program assistance made MSME actors familiar with digital accounting information systems.